2014
DOI: 10.5665/sleep.4180
|View full text |Cite
|
Sign up to set email alerts
|

Alteredin vitroEndothelial Repair and Monocyte Migration in Obstructive Sleep Apnea: Implication of VEGF and CRP

Abstract: Serum from OSA patient alters in vitro endothelial cell repair function and activates monocyte migration; this is further aggravated with the presence of metabolic syndrome. These effects are partly driven by VEGF and CRP, suggesting an unfavorable balance between the pro healing (VEGF) and pro injury (CRP) factors that may promote vascular injury in OSA with and without metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 33 publications
3
19
2
Order By: Relevance
“…We explored the effects of OSA during CPAP withdrawal on ADM, ET‐1 and VEGF, which are activated via HIF during hypoxic conditions. Cohort studies have suggested that these blood proteins play a role in cardiovascular disease in OSA . We found no increases in these markers during CPAP withdrawal.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…We explored the effects of OSA during CPAP withdrawal on ADM, ET‐1 and VEGF, which are activated via HIF during hypoxic conditions. Cohort studies have suggested that these blood proteins play a role in cardiovascular disease in OSA . We found no increases in these markers during CPAP withdrawal.…”
Section: Discussioncontrasting
confidence: 69%
“…Counter intuitively the increased ADM levels found in OSA have been proposed as an adaptive mechanism protective against cardiovascular disease . The effects of OSA on vascular endothelial growth factor (VEGF), an angiogenesis stimulator, are not clear …”
Section: Introductionmentioning
confidence: 99%
“…Similar to our results, Dyugovskaya et al 2002 isolated mononuclear cells from OSA and healthy patients and found increased monocyte adhesion to cultured endothelial cells [54]. Other studies examined monocyte migration following OSA serum incubation and found significant monocyte migration in patients with both moderate and severe AHI [55]. Apneic serum also demonstrated a significant increase in mesenchymal stem cell chemotaxis [56].…”
Section: Discussionsupporting
confidence: 87%
“…However, given the weak correlations ( r = 0.24–0.25), these factors are not likely to fully explain the observed differences in endothelial migration in our study. Other circulating factors previously shown to be unfavorably altered in individuals with MetS include plasma insulin, endothelin‐1, plasminogen activator inhibitor‐1, nitric oxide, C‐reactive protein, and interleukin‐6 (Briançon‐Marjollet et al ; Chedraui et al ; Ahirwar et al ). Future studies should seek to determine the specific circulating factors potentially contributing to impaired endothelial migration with MetS.…”
Section: Discussionmentioning
confidence: 99%